2007
DOI: 10.1002/jcp.21000
|View full text |Cite
|
Sign up to set email alerts
|

δ‐, but not µ‐, opioid receptor stabilizes K+ homeostasis by reducing Ca2+ influx in the cortex during acute hypoxia

Abstract: Past work has shown that delta-opioid receptor (DOR) activation by [D-Ala(2),D-Leu(5)]-enkephalin (DADLE) attenuated the disruption of K(+) homeostasis induced by hypoxia or oxygen-glucose deprivation (OGD) in the cortex, while naltrindole, a DOR antagonist blocked this effect, suggesting that DOR activity stabilizes K(+) homeostasis in the cortex during hypoxic/ischemic stress. However, several important issues remain unclear regarding this new observation, especially the difference between DOR and other opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 79 publications
6
80
0
Order By: Relevance
“…Soon after, we observed similar protection in the cortical neurons exposed to hypoxia [80]. Consistently, our electrophysiological studies with UFP-512 (H-Dmt-Tic-NH-CH[CH2-COOH]-Bid) [54], a more potent and specific DOR agonist, also showed that DOR is relatively specific in the protection against anoxic disruption of ionic homeostasis because MOR activation was not shown to induce any protective effect [55]. Furthermore, our transgenic studies showed that cortical DOR overexpression attenuated anoxia-induced disruption of ionic homeostasis, suggesting that an increase in DOR expression renders the cortex more tolerant to hypoxic stress [83].…”
Section: δ-Opioid Receptor: a Neuroprotector Against Hypoxic/ischemicsupporting
confidence: 65%
“…Soon after, we observed similar protection in the cortical neurons exposed to hypoxia [80]. Consistently, our electrophysiological studies with UFP-512 (H-Dmt-Tic-NH-CH[CH2-COOH]-Bid) [54], a more potent and specific DOR agonist, also showed that DOR is relatively specific in the protection against anoxic disruption of ionic homeostasis because MOR activation was not shown to induce any protective effect [55]. Furthermore, our transgenic studies showed that cortical DOR overexpression attenuated anoxia-induced disruption of ionic homeostasis, suggesting that an increase in DOR expression renders the cortex more tolerant to hypoxic stress [83].…”
Section: δ-Opioid Receptor: a Neuroprotector Against Hypoxic/ischemicsupporting
confidence: 65%
“…The box was rapidly cleaned daily when the animals were removed to have their body weights recorded. The rats of Groups B and D were subjected to an intraperitoneal injection of UFP-512 (H-Dmt-Tic-NH-CH[CH2-COOH]-Bid), a specific and potent DOR agonist synthesized by our team [28]. The injections (1 mg/kg in <1 ml) were performed on day 0 (immediately before the onset of hypoxia), day 4, and day 8.…”
Section: Methodsmentioning
confidence: 99%
“…The ␦-opioid receptor (DOR) plays a protective role in cerebral ischemia, hypoxia, cardiac dysfunction, skeletal muscle damage, peripheral organ survival, and vulnerability to stress (Borlongan et al, 2004;Hebb et al, 2005;Hong et al, 2005;Saitoh et al, 2005;Chao et al, 2007;Förster et al, 2007). Interestingly, CNS expression of DORs is often dynamically induced following physiological challenge (Commons, 2003;Hack et al, 2005;Cahill et al, 2007) and trafficking to the plasma membrane is regulated through a variety of mechanisms, which are dependent on stimulus type and duration (Cahill et al, 2007).…”
Section: Introductionmentioning
confidence: 99%